THE SIGNIFICANCE OF THE “ARI” METHOD IN TEACHING THE TRADITIONS OF UZBEK NATIONAL MUSICAL HERITAGE - Mansurova Nigoraxon Rustamjonovna (Western European Studies, 2025)
This article is devoted to the analysis of the proprietary “Ari” method technology, developed on the basis of innovative approaches for teaching samples of Uzbek national musical heritage. The method is grounded in unique musical traditions that have been transmitted through the master–apprentice (ustoz–shogird) system over generations. The teaching process, aimed at preserving the authenticity of performance features, modal (lad) structures, rhythmic movement (usul), and other national stylistic ornaments of musical heritage, requires an axiological approach to music education. The representation of the traditions of Uzbek national heritage through musical expressive means within modern musical notation has not yet been sufficiently studied. The application of the “Ari” method yields effective results in guiding the younger generation toward mastering national classical traditions, contributing to the development of their musical perception, aesthetic awareness, and appreciation of cultural values.
Keywords: National musical art; national classical music; maqom art